Development and validation of a teacher efficacy scale in the Indonesian context - Rozi Sastra Purna (Jurnal Psikologi Tabularasa, 2025)
Teacher efficacy plays a crucial role in determining the quality of learning and the success of the educational process. However, measurement instruments that are relevant to the Indonesian cultural and educational context remain limited. This study aims to develop and validate a Teacher Efficacy Scale in Indonesia. The scale construction was based on Bandura’s (1997) self-efficacy theory, which consists of three dimensions—level, strength, and generality—and followed the standard procedures for psychological scale development, including theoretical identification, conceptualization, operationalization, construction, content validity testing, construct validity testing, reliability analysis, and finalization. Participants consisted of 102 public elementary school teachers in Padang, Indonesia, all of whom were civil servants. Confirmatory Factor Analysis (CFA) was conducted through nine stages of item selection based on loading factors, standardized residual covariances, and modification indices. The final CFA model retained seven valid items with loading factors above 0.50 and demonstrated a good model fit (X² = 19.210; p = 0.057; GFI = 0.952; AGFI = 0.878; CFI = 0.982; TLI = 0.966; RMSEA = 0.086). The findings indicate that the developed scale possesses strong validity and reliability and can be used to measure teacher efficacy among Indonesian elementary school teachers. Practically, this instrument may serve as a valuable tool for research, psychological assessment, and teacher development programs aimed at enhancing professional competence.